A coproparasitological survey of gastrointestinal helminths in black vultures (Coragyps atratus) from Livingston, Izabal, Guatemala - Callejas-Martínez, Jessica (2019)
The aim of this study was to determine the presence of gastrointestinal helminths in black vultures (Coragyps atratus) from an area in Livingston, Izabal, Guatemala, using coproparasitological analysis. Thirty-two fecal samples from these birds were analyzed by the direct smear method and the saturated sugar solution flotation method. Out of the 32 analyzed fecal samples, 21 (65.6%) tested positive for gastrointestinal helminth ova and, out of these, 20 (95.2%) presented trematode ova, 3 (14.3%) nematode ova, and 1 (4.8%) acanthocephalan ova. Eggs of a trematode of the superfamily Diplostomoidea were the most commonly observed, being detected in 20 (62.5%) out of the 32 samples analyzed. Furthermore, samples contained trematode eggs from the family Echinostomatidae, nematode eggs from the genus Heterakis and the families Ascarididae and Trichostrongylidae, as well as eggs of Acanthocephala. Based on the coproparasitological analysis, the evaluated black vultures had gastrointestinal helminths, with the predominance of a trematode species of the superfamily Diplostomoidea. The findings of this research constitute the first approach to learning about the gastrointestinal helminthological fauna of Coragyps atratus in Guatemala.